Flood Hazard Mapping in Bandung Regency Based on Multi-Criteria Decision Analysis (MCDA) with AHP Method - Putra, Riki Purnama; Agustina, Rena Denya; Susanti, Seni; Chusni, Muhammad Minan; Novitasari, Emiliya (Indonesian Review of Physics, 2023)
Flooding is a natural disaster that can harm various parties, both harming nature and also harming humans. Floods can certainly hinder various human activities, both social and economic. Various causes of flooding can be caused by two main factors, namely natural factors and human factors. The natural factors in question are caused by nature, such as high-intensity rain, while the human factors are caused by humans, such as massive development and lack of drainage and humans' bad attitude towards the environment. This research aims to determine the probability of flooding in the Bandung Regency area. The research method used uses the Analytical Hierarchy Process (AHP) method based on Multi Criteria Decision Analysis (MCDA) using eight main factors, namely; (1) NDVI; (2) TWI; (3) Land Use; (4) Rainfall; (5) Slopes; (6) Elevation; (7) Distance from Road; and (8) Distance from River. Then the probability results are formed into a flood risk map for the Bandung Regency area with validation carried out using the ROC curve. The results obtained are that there are four risk categories, including; (1) Low Risk; (2) Quite Risk; (3) High Risk; and (4) Extreme Risk. The Bandung Regency area near Bandung City has the most High Risk to Extreme Risk, while outside that area has an average of Low Risk to Quite Risk. In addition, the validation results by comparing the obtained maps with the flood maps that occurred in 2002–2022 obtained an average ROC curve percentage of 76.4%, and these results show that the flood risk hazard map for Bandung Regency is valid.